Hesse’s Reader Who No Longer Reads in the Context of Modern Media - Piskač, Davor (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The article analyses several of Hesse’s essays, with an emphasis on the 1920 essay On Reading Books, from the perspective of modern literary studies, psychology, and neuroscience. In the essay, Hesse made his classification of literary readers and anticipated the emergence of the “reader who no longer reads” as a kind of the enlightened reader, a human being who, thanks to his/her deep and dedicated understanding of emotions in literature, has the meaning of his/her life at his/her fingertips, who understands what he/she thinks and especially what he/she feels. Thus, it is the reader who really understands his/her emotions. However, nowadays, in the age of digital media, a new version of the “reader who does not read” is emerging. Such a reader is an arrogant and superficial modern reader who believes he/she knows everything only because he/she can easily reach information he/she does not even really try to understand, and who hardly thinks about emotions in literature. Therefore, the second part of the article relies on two more of Hesse’s essays on reading literature, one of which anticipates the influence of multimedia on reading, and tries to explain the emergence of the modern “reader who does not read”. More specifically, the article here considers the ways how literature can foster emotions and experience in the age of digital multimedia. Namely, if we want to feel and experience while reading literature, we need to develop both the cognitive and the emotional apparatus willing and able to understand what is read, but the modern media seem to stand in the way. It is good to point out the problem, but it is even better to offer the possibility of problem-solving; thus, the third part of the article addresses new/old knowledge about the effects of reading aloud on the development of our emotional and cognitive abilities. Of course, the methods of reading aloud in the multimedia context already exist, and they are successful, so the article also presents a study on stimulating emotions and empathy by the method of reading aloud.